Theoretical analysis and model simulation of ADEF linearization technique for RF power amplifier unit - CHEN Chun-yu; LIN Mao-liu; XU Hong-guang (Tongxin xuebao)
The mechanism is analyzed in this paper that AM-AM conversion and AM-PM conversion can cause intermodulation (IM) disturbances of RF power amplifier unit,and the functional relation between the AM-AM conversion coefficient, AM-PM conversion coefficient and C/I3 is deduced. An adaptive double envelope feedback linearizer based on above theory is adopted to compensate the nonlinear characteristic of RF power amplifier unit. At last,themodel of ADEF linearizer is built and simulated. Results indicate that, because of the adoption of ADEF linearizer,the value of C/I3 reaches about 60dB.